FINE RESERVOIR DESCRIPTION techniques, current status, challenges and solutions. - CHEN, HUANQING (GULF PROFESSIONAL, 2022)
Fine Reservoir Description: Techniques, Current Status, Challenges and Solutions presents studies on fine oil and gas reservoirs, covering aspects of current status and progress, content and methods/techniques, as well as challenges and solutions through literature review and case studies of reservoirs, including volcanic rocks in the Songliao Basin, glutenite at the northwestern margin of the Junggar Basin, and sandstone in the Liaohe Basin, China. This book contains a large amount of data and illustrations.